2009
DOI: 10.1177/104063870902100201
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of a Multiplex Real-Time Reverse Transcription Polymerase Chain Reaction Assay for Detection of Vesicular Stomatitis Virus

Abstract: Abstract. Sporadic outbreaks of vesicular stomatitis (VS) in the United States result in significant economic losses for the U.S. livestock industries because VS is a reportable disease that clinically mimics footand-mouth disease. Rapid and accurate differentiation of these 2 diseases is critical because their consequences and control strategies differ radically. The objective of the current study was to field validate a 1-tube multiplexed real-time reverse transcription polymerase chain reaction (real-time R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Wells with cytopathic effect were confirmed as positive for VSNJV using rRT-PCR. Total RNA was extracted using the Qiagen RNeasy kit (Qiagen, Inc., Valencia, CA, U.S.A.) following the manufacturer's protocol, and stored at −20 • C. Viral RNA was detected by semi-quantitative rRT-PCR specific for the nucleocapsid gene of VSNJV, as described previously (Wilson et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Wells with cytopathic effect were confirmed as positive for VSNJV using rRT-PCR. Total RNA was extracted using the Qiagen RNeasy kit (Qiagen, Inc., Valencia, CA, U.S.A.) following the manufacturer's protocol, and stored at −20 • C. Viral RNA was detected by semi-quantitative rRT-PCR specific for the nucleocapsid gene of VSNJV, as described previously (Wilson et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…7,20 In recent years, a number of rapid diagnostic tests for VSV have been developed, 1,[4][5][6]17 including different real-time reverse transcription polymerase chain reaction (real-time RT-PCR) assays. 11,12,19 These assays, however, either lack diagnostic sensitivity and may miss some current circulating strains of the virus 11,12 or use a cumbersome combination of a large number of primers to ensure accurate and sensitive detection of strains of VSV by targeting the N gene of the virus. 19 A previous study 5 reported the development of a multiplex real-time PCR that targets the L gene of VSV.…”
mentioning
confidence: 99%
“…11,12,19 These assays, however, either lack diagnostic sensitivity and may miss some current circulating strains of the virus 11,12 or use a cumbersome combination of a large number of primers to ensure accurate and sensitive detection of strains of VSV by targeting the N gene of the virus. 19 A previous study 5 reported the development of a multiplex real-time PCR that targets the L gene of VSV. As part of the validation protocol of the assay, it was determined that the assay was not sensitive enough and failed to detect some of the current strains of the virus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cycling parameters were based on the previously reported real-time RT-PCR for Vesicular stomatitis virus. 30 The cycle temperatures were 55uC for 25 min, 95uC for 2 min, 40 cycles of 95uC for 10 sec, and 55uC for 1 min. The samples were analyzed using 3 real-time PCR instruments.…”
mentioning
confidence: 99%